Dilema Green Tax Administration: Studi Kasus Pendampingan BALAPIN dalam Navigasi Sistem Coretax 2026 - I Dewa Agung Nanditiya Putra; Made Andy Pradana Sukarta; Gede Teguh Prasetya Muttiwijaya; Ni Made Mega Abdi Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The transformation of tax administration in Indonesia through the implementation of the Coretax Administration System (Coretax), which began in 2025, marks a significant step in the modernization of digital tax systems. This implementation started to have a direct impact on the Annual Tax Return (SPT) reporting process in 2026 for the 2025 fiscal year. However, this transition also presents adaptation challenges for taxpayers in understanding the new interface and reporting procedures. This study aims to analyze taxpayer adaptation to the Coretax system and explore the role of the Bantu Lapor Pajak Integrasi (BALAPIN) program as an assistance mechanism for annual tax return reporting at Politeknik Negeri Bali. This research employs a qualitative case study approach through participatory observation and interviews conducted during the assistance activities. The findings reveal that taxpayers still encounter several administrative challenges, including difficulties in navigating the system, understanding certain tax status regulations, and managing the complexity of reporting income and assets. The involvement of tax volunteers and supervising lecturers in the BALAPIN program helps bridge tax literacy gaps and improve taxpayers’ understanding of the reporting process. These findings indicate that the success of digital tax administration depends not only on technological advancement but also on adequate literacy support and assistance mechanisms for users.